APPLICATION OF VIRTUAL REALITY TO THE ENHANCEMENT OF PHYSICAL ACTIVITY AND SPORTS FOR HEALTHY INDIVIDUALS. A SYSTEMATIC REVIEW - Milena Kuleva (Scientific Publishing House. NSA Press, 2023)
As technology advances, virtual reality (VR) becomes more prevalent in various fields of endeavor. Virtual reality is frequently associated with entertainment for adolescents. This is not always the case, however. Military, medicine, education, and architecture could all benefit from virtual reality, and in these fi elds, with complete confidence, sports and physical activity could also be added. As the origins of virtual reality are examined, it could be confirmed that people have always desired to recreate reality, beginning with drawings and progressing through cinema and photography to modern technologies that attempt to recreate the environment, real objects, states, etc., as accurately as possible. This study aims to analyze the available and accessible literature that has examined the application of different types of virtual reality. In order to fulfill the set objective, access through the virtual library of SUNY Empire State College was used. The researched databases were ProQuest, MEDLINE (with Full Text), PloS ONE, JSTOR, Library and Information Science and Technology Abstracts with FullText, EBSCOhost, LearnTechLib, Sage Journals, and Science Direct. The PRISMA guidelines were utilized to guide the review's conduct. The total number of sources studied was 2800, and through the PRISMA model, the final amount of analyzed articles was reduced to 11. According to the set inclusion and exclusion criteria, the articles considered comprehensively explained the methodology employed and delved into the effects of virtual reality on sports and physical activity among the participants. Virtual reality technology provides a personalized experience by adapting to the individual's interests and abilities. It has been discovered that immersive VR exergames can result in the same or greater exercise intensity than conventional exercise conditions. Exergaming in virtual reality could be especially beneficial for promoting physical activity and overall societal health.